Science of people and anthropology of man - Kovačević Ivan (Glasnik Etnografskog Instituta SANU, 2008)
A determination of a relationship between ethnology and anthropology with etymology as a starting point, loses a developmental dimension. Besides, a reduction in anthropology to the question:' What is a man' and discussion of 'general characteristics of human existence' represents reduction of anthropology to only one subject, which is the cause of the anthropology's marginalized position. On the other hand, a notion of ethnology is being discharged from the content by a break-up with a metaphysically constructed conception of 'folk spirit' and all the rest 'ethno' dispositions. Hence there is no point in discussing the relationship of a totally reduced anthropology and de-constructed ethnology. Current state of affairs within academically constituted disciplines in Serbia has shown that the vacancy originated by an ethnology de-construction was not filled in by anthropology, reduced to 'anthropology of Man' but a considerable 'anthropologization' of ethnological institutional frame.